Ten-year trend in prevalence and outcome of Down syndrome with congenital heart disease in a middle-income country - Zahari, Norazah; Mat Bah, Mohd Nizam; A. Razak, Hasliza; Thong, Meow Keong (Springer, 2019)
Limited data are available on the survival of patients with Down syndrome and congenital heart disease (CHD) from middle-income countries. This retrospective cohort study was performed to determine the trends in the prevalence and survival of such patients born from January 2006 to December 2015 in Malaysia. Among 754 patients with Down syndrome, 414 (55%) had CHD, and no significant trend was observed during the 10 years. Of these 414 patients, 30% had lesions that closed spontaneously, 35% underwent surgery/intervention, 9% died before surgery/intervention, and 10% were treated with comfort care. The overall mortality rate was 23%, the median age at death was 7.6 months, and no significant changes occurred over time. The early and late post-surgery/intervention mortality rates were 0.7% and 9.0%, respectively. Most deaths were of non-cardiac causes. The overall 1-, 5-, and 10-year survival rates were 85.5%, 74.6%, and 72.9%, respectively. Patients with severe lesions, persistent pulmonary hypertension of the newborn, atrioventricular septal defect, and pulmonary hypertension had low survival at 1 year of age. Conclusion: The prevalence of CHD in patients with Down syndrome is similar between Malaysia and high-income countries. The lower survival rate is attributed to limited expertise and resources which limit timely surgery.What is Known:• The survival of patients with Down syndrome with congenital heart disease (CHD) has improved in high-income countries. However, little is known about the survival of patients with Down syndrome with CHD from middle-income countries.• In the Caucasian population, atrioventricular septal defect is the most common type of CHD associated with Down syndrome.What is New:• In middle-income countries, the prevalence of CHD is the same as in high-income countries, but with a lower survival rate.• In the Asian population, ventricular septal defect is the most common type of CHD in patients with Down syndrome.